ย้อนร้อยพญานาคถอดเกล็ดประวัติศาสตร์นครเชียงตุง - และคณะ, ทรงศักดิ์ พรมดี (วารสารวิชาการพระพุทธศาสนาเขตลุ่มน้ำโขง; Vol 1 No 1 (2018): ปีที่ 1 ฉบับที่ 1 ประจำเดือนมกราคม - มิถุนายน 2561, 2018)
Kwangtung Chiang Tung plays an important role in the culture, religion, and morals of Chiang Tung, a city with a belief in snakes. It is important for landmarks such as Nong Tung or the temple. Snakes are believed to be very special animals. But the people of Chiang Tung do not believe in the importance of great worship. Snakes are associated with Buddhism from the present day to the present. Especially in the case of the priesthood, there must be something that is a symbol of the serpent. The town of Chiang Tung used to make gold candles and silver coins as Naga Tanaka. There are cultures related to Naga, such as the culture of the temple or the temple. It is very popular as a couple. Naga is a special animal with great power, a virtuous form of good deeds, such as the truth and the guardian of all ages. Keywords: History, Regence, Chiang Mai- Kwangtung